NCOG-01. STEREOTACTIC RADIOSURGERY FOR BRAIN METASTASES AT THE GUY’S CANCER CENTER, LONDON: AN AUDIT FOR THE FIRST 17 MONTHS - Bhadra, Kallol (Neuro Oncol, 2020)
INTRODUCTION: Stereotactic radiosurgery (SRS) commenced at Guy’s Cancer Hospital in August 2017. We report our first seventeen months’ data (August 2017 to December 2018) for brain metastases SRS. METHOD: Patients referred via Neuro Oncology MDT were assessed for suitability for SRS via clinical review and 1mm-slice MRI. Treatment was planned on Eclipse v15.6 and delivered using Truebeam STx Linac(FFF) and Align RT v5.1 for matching. Dose prescription, according to departmental protocol, was set at 100% isodose, ranging from 18Gy to 25Gy, with fractionation varying from single to five fractions depending on factors including size, volume and locations. Post-treatment, patients were discharged back to their primary treating team for 3-monthly MRI. RESULTS: Between Aug-17 to Dec-18, 70 patients with brain metastases were treated with a total of 122 lesions. Mean age was 66 years (range 37-93) and Median follow-up 9 months. Primary tumour sites mainly included lung 34(48.5%), breast 16(22.8%) and melanoma 17(24.3%). Brain-only metastases, including small volume primary with brain metastases were found in 85.4% cases, whilst visceral disease with brain metastases were found in 14.5% patients. Out of 122 lesions, the majority were treated in the primary setting; 95(77.8%) vs 27(22.1%) in the adjuvant setting. At 9-months follow up, local failure rate was in 26(21.3%) sites and 17 new sites in distant brain appeared. 31(44.2%) patients received no systemic therapy after SRS, whilst immunotherapy was received by 14(20%), with the remaining receiving hormones or chemotherapy. Median Overall Survival was 9.2 months (95% CI: 4.5-13.8) and Median progression-free survival was 5.9 months (95% CI: 7.0-10.4). CONCLUSION: Overall Survival results were encouraging with initial auditing proving SRS as effective approach. Local control rates correlate well with randomized control trials results for SRS in brain metastases.